1998
DOI: 10.1021/tx9801209
|View full text |Cite
|
Sign up to set email alerts
|

Thioether Adducts of a New Imine Reactive Intermediate of the Pneumotoxin 3-Methylindole

Abstract: Cytochrome P450 enzymes can potentially oxygenate 3-methylindole to form 2,3-epoxy-3-methylindoline which could rearrange to the stable metabolite 3-methyloxindole or open to form 3-hydroxy-3-methylindolenine, a putative electrophilic imine. The purpose of the current work was to determine if the imine was formed, and to characterize it via its adducts with thiol nucleophiles. Thiols were added to incubations of goat lung microsomes with 3-methylindole and deuterated analogues of 3-methylindole to trap the imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 8 publications
(12 reference statements)
2
32
0
Order By: Relevance
“…In one such experiment, 3-glutathionyl-S-3-methyloxindole, a thioether adduct at the C-3 position of the 2,3-epoxide, was identified in metabolic reactions of 3MI with GSH-fortified human liver microsome (Yan et al, 2007). Additional studies showed that 3-methyl-2-glutathionyl-Sindole was not derived primarily from MEI in human liver microso- mal reactions and that the corresponding NAC adduct was not primarily derived from MEI in goat lung microsomal reactions (Skordos et al, 1998a;Yan et al, 2007). The studies presented here have identified MOI and most likely HMI as products of CYP2A13-mediated 3MI metabolism, a result suggesting that CYP2A13 catalyzes the epoxidation of 3MI.…”
Section: Discussionmentioning
confidence: 94%
“…In one such experiment, 3-glutathionyl-S-3-methyloxindole, a thioether adduct at the C-3 position of the 2,3-epoxide, was identified in metabolic reactions of 3MI with GSH-fortified human liver microsome (Yan et al, 2007). Additional studies showed that 3-methyl-2-glutathionyl-Sindole was not derived primarily from MEI in human liver microso- mal reactions and that the corresponding NAC adduct was not primarily derived from MEI in goat lung microsomal reactions (Skordos et al, 1998a;Yan et al, 2007). The studies presented here have identified MOI and most likely HMI as products of CYP2A13-mediated 3MI metabolism, a result suggesting that CYP2A13 catalyzes the epoxidation of 3MI.…”
Section: Discussionmentioning
confidence: 94%
“…Even with Ser which produced adducts without S9, adducts levels were higher with S9, indicating that metabolic activation also plays an important role in Ser-induced adducts. In the case of 3MI, cytochrome P450-mediated epoxidation of the imidazole ring or hydroxylation/dehydrogenation of the methyl group has been shown to produce reactive intermediates, which can form adducts with glutathione, N-acetylcysteine, proteins, and DNA [Skiles and Yost, 1996;Kaster and Yost, 1997;Skordos et al, 1998;Regal et al, 2001]. These routes of metabolic activation may also be involved in the formation of electrophiles from Mel, Ser, and Tryp.…”
Section: Discussionmentioning
confidence: 99%
“…NAC has a simpler structure compared with GSH, making the analysis of MS/MS spectra of the trapped adducts less complicated. In addition, NAC has been used successfully for trapping reactive imine intermediates (Skordos et al, 1998a). NAC adducts of PCP were formed from incubations with 2B6 and observed at R t 18.9 and 19.13 min with an m/z value of 437 (data not shown).…”
Section: Shebley Et Almentioning
confidence: 99%